Enantioselective Copper-Catalyzed Allylic/Propargylic Acyloxylation: Asymmetric Variants of the Kharasch–Sosnovsky Reaction - Tang, Sheng; Yu, Shouyun (Synthesis, 2025)
Copper-catalyzed enantioselective allylic/propargylic acyloxylation, evolving from the classical Kharasch–Sosnovsky reaction, has emerged as a versatile strategy for the stereocontrolled synthesis of chiral esters. This short review comprehensively summarizes recent advances in asymmetric variants of Kharasch–Sosnovsky reaction across three primary substrate categories: cyclic olefins, acyclic alkenes/alkynes, and 1,3-dienes/enynes, with particular emphasis on substrate scope and mechanistic insights.
Keywords: Asymmetric catalysis; Copper; Kharasch–Sosnovsky oxidation; Allylic; Propargylic; Acyloxylation